Association of serum nitric oxide metabolite level with mortality in patients undergoing coronary angiography. Issue 6 (December 2022) - Namba, Takayuki; Masaki, Nobuyuki; Hitomi, Yasuhiro; Ishinoda, Yuki; Iwashita, Midori; Yumita, Yusuke; Kagami, Kazuki; Yasuda, Risako; Ikegami, Yukinori; Toya, Takumi; Nagatomo, Yuji; Takase, Bonpei; et al.
Abstract: Background: Nitric oxide (NO) is a relevant molecule for vascular homeostasis. The level of serum NO metabolites (NOx), which consist of nitrite and nitrate, has been investigated as an alternative biomarker of NO production, but its clinical value has not yet been determined. Methods and results: 143 patients (66 ± 12 years old) were followed up after coronary catheterization. During a median (inter-quartile range) observation period of 6.13 (3.32–9.21) years, there were 20 (14 %) all-cause deaths, including 11 (8 %) cardiovascular deaths, 17 (12 %) major adverse cardiovascular events, and 17 (12 %) hospital admissions for heart failure. Median NOx level was 34.5 μmol/L (23.9–54.3). NOx was a risk factor for all-cause death [hazard ratio (HR) by unit increase, 1.010, 95 % confidence interval (CI) 1.001–1.018; p = 0.021] and heart failure (HR 1.010, CI 1.001–1.019; p = 0.029). Even after adjustment for age, sex, coronary risk factors, C-reactive protein, log-transformed brain natriuretic peptide, estimated glomerular filtration rate, and nitrate treatment, NOx was a risk factor for all-cause death (HR 1.015, CI 1.004–1.027; p = 0.008) and admission with heart failure (HR 1.018, CI 1.005–1.018, p = 0.007). Conclusions: An increase in serum NOx level does not herald a benign clinical course but is an independent predictor of high risk of any-cause mortality and heart failure. Graphical abstract: Unlabelled Image Highlights: NO metabolites (NOx) have been studied as a biomarker of NO production. In the observation, elevated serum NOx level was a predictor of all-cause death. Serum NOx level was positively correlated with diacron reactive oxygen metabolites, an oxidative stress marker.